2014
DOI: 10.1001/jamadermatol.2013.9517
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Teledermatology to Triage Inpatient Dermatology Consultations

Abstract: Teledermatology is reliable for the triage of inpatient dermatology consultations and has the potential to improve efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 35 publications
(37 reference statements)
3
72
0
3
Order By: Relevance
“…[19][20][21][22][23][24]26 As a result of smartphone-based digital cameras, most people now have basic familiarity with image capture and sharing. 41 Prior survey-based work suggested that most patients would be willing to use smartphones for wound surveillance after vascular surgery procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24]26 As a result of smartphone-based digital cameras, most people now have basic familiarity with image capture and sharing. 41 Prior survey-based work suggested that most patients would be willing to use smartphones for wound surveillance after vascular surgery procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Classically known as "store-and-forward" telemedicine, this approach has been used successfully to provide clinical assessments and follow-up care in dermatology, plastic surgery, and burn care. [19][20][21][22][23][24][25] Often, these images are captured by a clinician in one setting and shared with another clinician elsewhere. To date, there has been minimal incorporation of these new care delivery modalities into general surgical care, and patients have been less frequently relied upon to generate their own data in the form of digital images.…”
mentioning
confidence: 99%
“…There was a predominance of female sex in six studies, 5,36,40,45,46,50 male predominance in two studies, 41,43 and no information about sex in nine studies. Participants' age also varied, ranging from infants to elderly patients.…”
Section: Study Qualitymentioning
confidence: 92%
“…42 The remaining studies encompassed multiple skin conditions. 7,36,37,40,[45][46][47][50][51][52] Twelve studies analyzed the reliability by kappa statistics. 5,36,[38][39][40][41][42][44][45][46]48,50 From these, one study compared teledermatology and FTF diagnosis to histopathological results, 39 one compared both groups to teledermatology and FTF diagnosis to the definitive diagnosis, 40 all the others considered FTF consultation as standard reference without histopathological confirmation for the diagnosis.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation